Analysis of Interest in Participating in Rugby Sports for Students of SMK Negeri 3 Salatiga - Maulida Mina; Gatot Jariono (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This research was conducted through a preliminary study and the results of a survey on students of SMK Negeri 3 Salatiga related to the interest in participating in the sport of Rugby. The purpose of this study was to find out how interested the students of SMK Negeri 3 Salatiga were in participating in the sport of Rugby. The main problem in this study is not yet known how much students are interested in participating in rugby sports. The method used in this study uses descriptive quantitative analysis with the research technique used is a questionnaire. This research was carried out at SMK Negeri 3 Salatiga in June 2022 with a total sample of 95 people consisting of 10 Ototronic 1, Ototronic 2, Ototronic 3, Welding 1, and Welding 2 classes. the statement is declared valid and reliable or feasible to use, it is continued with the Factor Analysis Test which of the 4 indicators there are 9 factors, and the overall results of SMA Negeri 3 Salatiga are appropriate. Of the 9 factors, 6 said it was quite suitable, 1 said it was very suitable, and 2 said it was slightly suitable. Thus, this proves that students of SMK Negeri 3 Salatiga are interested in participating in rugby.